Safety plugins for risks prevention through design resourcing BIM. Issue 2 (26th October 2020) - Rodrigues, Fernanda; Antunes, Flávio; Matos, Raquel
Abstract : Purpose: The use of building information modelling (BIM) methodology has been increasing in the architecture, engineering, construction and operation sector, driven to a new paradigm of work with the use of three-dimensional (3D) parametric models. However, building information modelling (BIM) has been mostly used for as-built models of a building, not yet been widely used by designers during project and construction phases for occupational risks prevention and safety planning. This paper aims to show the capacity of developing tools that allow adding functionalities to Revit software to improve safety procedures and reduce the time spent on modelling them during the design phase. Design/methodology/approach: To reach this objective, a structural 3D model of a building is used to validate the developed tools. A plugin prototype based on legal regulations was developed, allowing qualitative safety assessment through the application of job hazard analysis (JHA), SafeObject and checklists. These tools allow the automated detection of falls from height situations and the automated placement of the correspondent safety systems. Findings: Revit application programming interface allowed the conception and addition of several functionalities that can be used in BIM methodology, and more specifically in the prevention of occupational risks in construction, contributing this paper to the application of a new approach to the prevention through design. Originality/value: This paper is innovative and important because the developed plugins allowed: automated detection of potential falls from heights in the design stage; automated introduction of safety objects from a BIM Safety Objects Library; and the intercommunication between a BIM model and a safety database, bringing JHA integration directly on the project. The prototype of this work was validated for fall from height hazards but can be extended to other potentials hazards since the initial design stage.